Teleconnections of Large-Scale Climate Patterns to Regional Drought in Mid-Latitudes: A Case Study in Xinjiang, China - Ruting Yang; Bing Xing (Atmosphere, 2022)
Drought is one of the most important environmental disasters. Assessment of the effects of oceanic atmospheric oscillations upon regional drought behavior has valuable implications for water resources management, especially for arid regions. This study aims to explore the climate drivers of drought conditions in Xinjiang, an arid region in mid-latitude Asia. Standardized Precipitation Evapotranspiration Index (SPEI) was adopted to describe drought variation over Xinjiang during the period of 1951–2020. Teleconnection effects of El Niño Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), Atlantic Multidecadal Oscillation (AMO), and Arctic Oscillation (AO) on Xinjiang drought variability were analyzed based on cross-correlation and stepwise regression methods. Partial correlation analysis was applied to discuss the responding mechanism of drought behavior to teleconnection signals from the perspective of regional climate factors. Findings from this study indicate that synchronous ENSO featured by Nino3.4 index has a significant positive correlation with Xinjiang dry/wet variation. El Niño may favor to wetness in Xinjiang, while La Niña may exacerbate drought effect in the region. ENSO mainly acts on the short-term drought variability in Xinjiang region. The synchronous PDO makes a leading contribution on drought variation at 12-month time scale among the four signals. The significant positive correlation between PDO and drought variation suggests that positive-phase (negative-phase) PDO may contribute to wetting (drying) epochs in Xinjiang region. AMO indicates a significant negative correlation with Xinjiang drought on both synchronous and asynchronous modes. Positive (negative) phase AMO may favor to dry (wet) effects in Xinjiang. AMO appears a predominant teleconnection effect on long-term drought variability, and fluctuates a persistent anti-phase mode with Xinjiang dry/wet variability since the mid-1980s. AO mainly acts on short-term drought fluctuations, indicating a significant negative correlation with drought behavior within a 12-month moving time window. Positive (negative) phase AO may contribute to dry (wet) epochs over Xinjiang. ENSO and PDO affect short-term dry/wet variation mainly through the teleconnection effect on precipitation variability. AMO mainly influences Xinjiang drought evolution by acting on regional temperature variation. The influence of internal atmospheric variability on regional climate behavior has a delayed effect, and drought variability is affected by precursor pattern of teleconnection likewise.